Investigating the Compositional Heterogeneity of Pure, Crystalline Plagioclase Exposures within the Moon’s Anorthositic Crust Using Moon Mineralogy Mapper and Diviner Data - Mélissa Martinot; Kerri L. Donaldson Hanna; Benjamin T. Greenhagen; Luis Santori; Patrick N. Peplowski; Joshua T. S. Cahill (The Planetary Science Journal)
Questions about the formation of the primary anorthositic crust of the Moon remain unanswered. Spectroscopic surveys of the lunar crust have evidenced the presence of pure, crystalline plagioclase exposures (PCPEs) across the surface, which are assumed to be remnants of the Moon's ancient anorthositic crust. Results from our work show that the plagioclase composition within PCPEs in all geochemical terranes is relatively uniform and consistent with highly calcic anorthite found in immature and mature Apollo highlands regolith samples. Observed variations in our spectroscopic data sets are likely related to maturity, not plagioclase composition, supporting a single crust-forming event rather than serial magmatism. To constrain the plagioclase composition within the primary anorthositic crust, we use remote sensing data from two instruments on board different lunar orbiters, Moon Mineralogy Mapper (M ^3 ) and Diviner Lunar Radiometer (Diviner). When working with data sets acquired by different instruments, coregistration is key if one wants to extract values from those instruments at the same point on the lunar surface. Due to the suboptimal selenolocation of the M ^3 observations, misalignments exist between the M ^3 data and Diviner data sets. Here we present a methodology for extracting both data sets from a single locality while mitigating offsets, and provide results about the composition of the primary anorthositic crust. M ^3 was used to identify regions of interest within previously reported PCPEs at a selection of craters, and Diviner Christiansen feature data was utilized to constrain these locations’ plagioclase composition by comparing them against laboratory measurements of Apollo 16 highland soil samples.